1993
DOI: 10.3189/s0022143000016348
|View full text |Cite
|
Sign up to set email alerts
|

Micro-earthquakes beneath Ice Streams Β and C, West Antarctica: observations and implications

Abstract: Micro-earthquakes have been monitored at two locations on Ice Stream Β and one on Ice Stream C using a seismographic array built specifically for that purpose. Subglacial micro-earthquakes arc 20 times more abundant beneath Ice Stream C than beneath Ice Stream B, despite the 100 times more rapid movement of Ice Stream B. Triangulation shows the foci beneath Ice Stream C, like those beneath Ice Stream B, to be within a few meters of the base of the ice, presumably within the uppermost part of the bed, and fault… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
106
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 27 publications
9
106
0
Order By: Relevance
“…High‐frequency seismic signals associated with glaciated environments have been recorded in Greenland, Antarctica, and Alaska and are known to be complex (e.g., Amundson et al, ; Anandakrishnan & Bentley, ; MacAyeal et al, ; O'Neel et al, ; Rial et al, ). High‐frequency seismic signals originate from stick‐slip motion at the ice‐bed interface in Western Greenland (Röösli, Helmstetter, et al, ) but generate higher frequencies (20–200 Hz) than we observe and appear to be observable only at very short distances.…”
Section: Discussionmentioning
confidence: 99%
“…High‐frequency seismic signals associated with glaciated environments have been recorded in Greenland, Antarctica, and Alaska and are known to be complex (e.g., Amundson et al, ; Anandakrishnan & Bentley, ; MacAyeal et al, ; O'Neel et al, ; Rial et al, ). High‐frequency seismic signals originate from stick‐slip motion at the ice‐bed interface in Western Greenland (Röösli, Helmstetter, et al, ) but generate higher frequencies (20–200 Hz) than we observe and appear to be observable only at very short distances.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to impulsive events that are typically recorded on ice streams [ Anandakrishnan and Bentley , 1993; Smith , 2006], we recorded two events, which we refer to as harmonic‐tremor events, of a type that has not been previously reported from Antarctica (Figures 2a and 2b). The events occurred two weeks apart (on days 348 and 365 of 2005), and are distinguished by: 1) durations of approximately 10 minutes, and 2) nearly monochromatic energy centered at a frequency of 3 Hz (Figure 2).…”
Section: Seismic Observations Of Glacial Tremormentioning
confidence: 96%
“…As we argue below, a subglacial outburst flood that drained from one lake to a second lake can explain these phenomena. Subglacial icequakes that are generated by stick‐slip basal motion produce impulsive broadband signals [ Anandakrishnan and Bentley , 1993], and ordinary crevassing events are also broadband sources [ Deichmann et al , 2000], both inconsistent with the observed tremors. In contrast, the long‐duration monochromatic nature of the MacIS tremors is similar to harmonic tremors observed in volcanic settings that originate from the resonance of magma‐filled conduits [ Chouet et al , 1994; Julian , 1994].…”
Section: Source Mechanismmentioning
confidence: 99%
“…The stick‐slip events can be triggered by stress changes through the tidal‐influenced floating ice shelves [e.g., Zoet et al , ; Winberry et al , ] or by lateral changes in till rheology [ Smith et al , ]. Both long‐duration slip events (lasting tens of minutes) [e.g., Winberry et al , ; Walter et al , ] and microseismicity (lasting fractions of a second) in the form of basal icequakes [e.g., Blankenship et al , ; Anandakrishnan and Bentley , ; Smith , ; Danesi et al , ] indicate that we need to consider coseismic slip in addition to viscous flow and basal sliding in the physical models for ice stream flow [ Goldberg et al , ; Tsai et al , ].…”
Section: Introductionmentioning
confidence: 99%